Synthesis of 3-Iodomethyl Sultams - Filimonchuk, Sergiy L.; Nazarenko, Kostiantyn; Shvydenko, Tetiana; Shvydenko, Kostiantyn; Rusanov, Eduard; Tolmachev, Andrei; Kostyuk, Aleksandr (Synlett, 2020)
A method for the synthesis of iodomethyl-substituted five-membered sultams has been developed. The sultams were synthesized by intramolecular iodoamination of alkenyl sulfamides. The method allows synthesis of N- and C-substituted sultams. NH-Sultams were prepared by acidic cleavage of the corresponding tert-butyl sultams that are readily available. Varying the length of alkenyl substituent at sulfamide it was shown that only five- and six-membered sultams could be prepared by this method. Neither four- nor seven-membered sultams were detected. The simple practical procedure and available starting materials make the variously substituted sultams readily available.
Keywords: sultam; iodoamination; sulfamide; iodine; cyclization